N-benzyladriamycin-14-valerate (AD 198) exhibits potent anti-tumor activity on TRAF3-deficient mouse B lymphoma and human multiple myeloma - Edwards, Shanique K E (BioMed Central, 2013)
BACKGROUND: TRAF3, a new tumor suppressor identified in human non-Hodgkin lymphoma (NHL) and multiple myeloma (MM), induces PKCδ nuclear translocation in B cells. The present study aimed to evaluate the therapeutic potential of two PKCδ activators, N-Benzyladriamycin-14-valerate (AD 198) and ingenol-3-angelate (PEP005), on NHL and MM. METHODS: In vitro anti-tumor activities of AD 198 and PEP005 were determined using TRAF3(-/-) mouse B lymphoma and human patient-derived MM cell lines as model systems. In vivo therapeutic effects of AD 198 were assessed using NOD SCID mice transplanted with TRAF3(-/-) mouse B lymphoma cells. Biochemical studies were performed to investigate signaling mechanisms induced by AD 198 or PEP005, including subcellular translocation of PKCδ. RESULTS: We found that AD 198 exhibited potent in vitro and in vivo anti-tumor activity on TRAF3(-/-) tumor B cells, while PEP005 displayed contradictory anti- or pro-tumor activities on different cell lines. Detailed mechanistic investigation revealed that AD 198 did not affect PKCδ nuclear translocation, but strikingly suppressed c-Myc expression and inhibited the phosphorylation of ERK, p38 and JNK in TRAF3(-/-) tumor B cells. In contrast, PEP005 activated multiple signaling pathways in these cells, including PKCδ, PKCα, PKCϵ, NF-κB1, ERK, JNK, and Akt. Additionally, AD198 also potently inhibited the proliferation/survival and suppressed c-Myc expression in TRAF3-sufficient mouse and human B lymphoma cell lines. Furthermore, we found that reconstitution of c-Myc expression conferred partial resistance to the anti-proliferative/apoptosis-inducing effects of AD198 in human MM cells. CONCLUSIONS: AD 198 and PEP005 have differential effects on malignant B cells through distinct biochemical mechanisms. Our findings uncovered a novel, PKCδ-independent mechanism of the anti-tumor effects of AD 198, and suggest that AD 198 has therapeutic potential for the treatment of NHL and MM involving TRAF3 inactivation or c-Myc up-regulation.